Obesity psychological treatment: beyond cognitive and behavioral therapy - Volery, M; Bonnemain, A; Latino, A; Ourrad, N; Perroud, A (Revue médicale suisse, 2015)
The psychological assessment of the patient with obesity aims to identify the factors of maintenance of excess weight, such as eating disorders or anxio-depressive disorders. Psychotherapy helps a better weight management. Cognitive-behavioral therapy has shown its effectiveness in the treatment of obesity. New psychotherapeutic approaches are explored. The hypnosis and mindfulness are proposed for the management of emotions and stress. A targeted approach on the body image disorder decreases body dissatisfaction. When post-traumatic stress syndrome is involved, EMDR (Eye Movement Desensitization & Reprocessing) is better than other types of therapies. Family therapy is indicated when the entourage is impacted. Psychological difficulties should be the subject of specific care.